Field biology of the cassava mealybug, Phenacoccus manihoti, and its natural enemies in Zaire - Muaka, T.; Hennessey, R.D. (1987)
Three severe outbreaks of cassava mealybug (CM), Phenacoccus manihoti, have occurred in Zaire. Two were associated with droughts. The third occurred in the driest part of the country and ended only when nearly all cassava plants had been killed. Native coccinellid predators sometimes greatly reduced CM populations, but only after the cassava crop had been heavily damaged. The exotic coccinellid Diomus sp. may be an effective biological control agent in Kinshasa, where CM on a hybrid form of cassava remained common during the rainy season. CM populations in Kinshasa declined greatly in the second year after the release of the exotic parasitoid Epidinocarsis lopezi. In one study the number of mummies with E. lopezi increased with host densities up to 20 CM per shoot tip. Since CM populations remained low after the releases of E. lopezi it is tentatively concluded that E. lopezi, despite considerable rates of hyperparasitism, prevents CM outbreaks over the whole area of its distribution (130,000 km2) in western Zaire.